Parametric design performance oriented - Cavieres, Andrés (Universidad de Chile. Facultad de Arquitectura y Urbanismo, 2007)
This article presents the concept of building performance and shows how BIM models can support design processes that focus on performance optimization. Parametric modeling is discussed as a key technology for such optimization since it allows for the computational generation of design alternatives. The potentials for collaborative and multidisciplinary design promoted by domain expertise embedded in parametric models, is also reviewed in the context of sustainable design, structural analysis and fabrication.